2017
DOI: 10.1002/jso.24678
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic utility of the “Tumor Burden Score” based on preoperative radiographic features of colorectal liver metastases

Abstract: Imaging-based TBS was superior to traditional tumor size and number and was comparable to pathology-based TBS. Imaging-based TBS may have the potential to facilitate improved preoperative risk stratification of patients with CRLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 33 publications
0
42
1
1
Order By: Relevance
“…Of note, TBS was calculated using pathological data, rather than preoperative radiographic imaging. However, the authors recently demonstrated that TBS values estimated by either imaging or pathology are equivalent in prognostic terms. As such, although pathological data were used to estimate TBS and consequently the GAME score in the present study, it is probable that the GAME score can also be calculated with the aid of imaging, supporting the decision to classify TBS as a value available before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, TBS was calculated using pathological data, rather than preoperative radiographic imaging. However, the authors recently demonstrated that TBS values estimated by either imaging or pathology are equivalent in prognostic terms. As such, although pathological data were used to estimate TBS and consequently the GAME score in the present study, it is probable that the GAME score can also be calculated with the aid of imaging, supporting the decision to classify TBS as a value available before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In solid tumors, such as melanoma, breast cancer, and lung cancer, tumor burden is always represented as the tumor size assessed using a CT scan [17]. However, as a hematopoietic and lymphoid disease, CT scan is not always performed to assess the tumor burden in DLBCL due to the large number of lymph nodes involved, as well as tumors in extra-nodal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor burden is thought to be an important risk factor in multiple malignancies, usually reflecting the degree of tumor damage to the body [17, 18]. In solid tumors, such as melanoma, breast cancer, and lung cancer, tumor burden is always represented as the tumor size assessed using a CT scan [17].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the TB score was defined as the distance from the origin on a Cartesian plane that incorporated 2 variables: maximum tumor size ( x -axis) and the number of liver lesions ( y -axis). The Pythagorean theorem was then used to calculate the distance of any given point from the origin of the plane (0, 0), whereby [TBS 2 = (maximum tumor diameter) 2 + (number of liver lesions) 2 ] [7, 8].…”
Section: Methodsmentioning
confidence: 99%
“…Mazzaferro et al [5, 6] demonstrated that the tumor size and number criteria for HCC have undergone numerous iterations culminating in a predictive tool termed the “metro-ticket” system. Furthermore, Sasaki et al [7, 8] showed that the “metro-ticket” concept was applicable to patients undergoing liver resection for colorectal liver metastases, and they established a novel scoring system (i.e., Tumor Burden (TB) score).…”
Section: Introductionmentioning
confidence: 99%